Vitis vinifera Turkish grape cultivar Karaerik. Part I: anthocyanin composition, and identification of a newly found anthocyanin. (20th December 2019) - Hermosín‐Gutiérrez, Isidro; Gómez‐Alonso, Sergio; Pérez‐Navarro, José; Kurt, Aynur; Colak, Nesrin; Akpınar, Erdal; Hayirlioglu‐Ayaz, Sema; Ayaz, Faik Ahmet
Abstract: BACKGROUND: Grape berries exhibit various beneficial health effects due to the potent antioxidant roles of their phenolic compounds. A new Vitis vinifera grape cultivar (Karaerik) grown in Turkey has attracted growing interest due to its antioxidant phenolic compounds, which have still not been investigated. The phenolic/anthocyanin profile needs to be investigated to ascertain its potential health benefits and market value in the region. The present study therefore involves a detailed characterization of the anthocyanin composition of 'Karaerik' grape berries in conjunction with a determination of the antioxidant capacity value of the phenolics present in the skin and the whole berry. RESULTS: Total phenolic compounds (average 8.56 and 2.88 g gallic acid equivalent kg −1 fresh weight) and anthocyanin (7.48 and 1.66 g mv‐3‐glc equivalent kg −1 fresh weight) contents varied significantly in the skin and whole berry. Malvidin‐based anthocyanins made the highest contribution to the pigment content of the berry. Accordingly, the major anthocyanin in the skin (average 42.08 mol%) and whole berry (39.98 mol%) was malvidin‐3‐glucoside (mv‐3‐glc). In addition, we found strong evidence of the occurrence of sometimes reported malvidin‐3‐pentoside and particularly of the not previously reported feruloyl derivative of malvidin‐3‐(6″‐feruloyl)‐glucoside (mv‐3‐ferglc) for V. vinifera grapes. CONCLUSION: The current study is the first report to profile the anthocyanins of the grape with a detailed description of the rare and novel anthocyanin in V. vinifera grapes. The berry is also a potential source of phenolics/anthocyanins with a high antioxidant capacity value and is worthy of comparison with other V. vinifera grapes. © 2019 Society of Chemical Industry